Hotspots and the geographies of humanitarianism. (December 2020) - Pallister-Wilkins, Polly
This article focuses on the humanitarian geographies of the hotspots. It argues that hotspots are humanitarian in both idea and practice by raising two fundamental questions that form the basis for the article: what is humanitarianism, and who is it for? The article understands humanitarianism as a logic of government that is more expansive than the mainstream ideal that emerged in the 20th-century. Instead humanitarianism is understood as concerning logics developed to both effectively manage disaster and to secure (in both senses of the word) imminently mobile populations for the maintenance of liberal order alongside and through the securing of life. The article takes an expansive view of humanitarian government to consider genealogies of caring and population security logics in the establishment of modern, western and liberal states. The article unsettles some of the traditional geographical understandings of humanitarianism as care for distant strangers and considers the ways compassion is rationalised by the hotspot approach. This critical reading of humanitarianism and the hotspots offers empirical weight to what has been called 'humanitarianism as liberal diagnostic', through which humanitarianism is deployed to secure both life and a liberal political order across multiple scales.